Investigating the burden of acute and chronic typhoid fever and the relative contribution to ongoing transmission of salmonella typhi in three urban sites in Africa and Asia - Meiring, J (2020)
Enteric fever is a serious public health concern in many low- and middle-income countries. However, numerous data gaps exist concerning the epidemiology and transmission of Salmonella Typhi and Paratyphi A, the causative agents of enteric fever, in different global contexts. Facility-based passive surveillance for enteric fever underestimates true incidence of disease as not all cases of infection can be captured. In typhoid endemic sites, where febrile illness is a common clinical syndrome, there are many healthcare facilities that individuals utilise when they develop fever. In addition, blood-culture, the current gold-standard for typhoid diagnosis, is not collected on all individuals who seek healthcare within a healthcare facility. Blood-culture also has a low sensitivity for diagnosis and is affected by prior antimicrobial usage and the volume of blood collected. A proportion of acutely infected individuals develop chronic carriage of Salmonella Typhi with the pathogen resident in the gall bladder. These individuals continue to shed the bacteria in their stool contributing to ongoing transmission within their community. It is not known what the prevalence of these chronic carriers are in endemic sites and the relative contribution of transmission from carriers compared with acutely infected individuals.